Indirect coal liquefaction by integrated entrained flow gasification and Rectisol/Fischer–Tropsch processes for producing automobile diesel substitutes. (15th March 2021) - Ra, Ho Won; Mun, Tae-Young; Hong, Sung Jun; Chun, Dong Hyun; Lee, Ho Tae; Yoon, Sung Min; Moon, Ji Hong; Park, Sung Jin; Lee, Seok Hyeong; Yang, Jung Hoon; Kim, Jae-Kon; Jung, Heon; et al.
Abstract: Herein, we describe the design and operation of an indirect coal liquefaction plant with integrated coal-water slurry manufacturing, entrained flow gasification, Rectisol, and Fischer–Tropsch processes to produce liquid fuels for vehicles. The above plant contained an entrained flow gasifier (10 t/d test rig) operated using oxygen as a gasifying agent (21 bar, 1100 °C) and could stably produce synthesis gas (37.8 vol% H2, 36.4 vol% CO) at 600 Nm 3 /h. Due to the importance of impurities in synthetic liquid fuel production, more than 99% of H2 S contained in synthesis gas was removed by the Rectisol process employing refrigerated methanol. An iron-based catalyst allowed liquid fuels containing wax, light/heavy oil, and alcohol fractions to be obtained by the Fischer–Tropsch process at a rate of 5 barrel per day, with detailed analysis confirming their compliance with various quality standards and thus their suitability for use as automobile diesel after distillation. Highlights: Integrated entrained flow gasifier and Rectisol/Fisher-Tropsch process was described. The synthesis gas (37.8 vol% H2, 36.4 vol% CO) at 600 Nm 3 /h was produced. More than 99% of H2 S contained in synthesis gas was removed in Rectisol process. The liquid fuels can be successfully produced by pilot-scale F-T synthesis. Distilled ICTL diesel can be a viable alternative for the commercial diesel.